Exploring the Role of Digital HR Analytics in Enhancing Human Resource Management Effectiveness - Risza Putri Elburdah; Muhammad Ramdhan (Poltanesa, 2026)
This study aims to explore the role of Digital HR Analytics in enhancing Human Resource Management (HRM) effectiveness. A qualitative research approach was employed to gain an in-depth understanding of how analytics is utilized in HR practices. Data were collected through semi-structured interviews with HR professionals and organizational leaders who are directly involved in HR decision-making processes. The data were then analyzed using thematic analysis to identify key patterns, themes, and insights. The findings indicate that Digital HR Analytics plays a significant role in improving HRM effectiveness through four major dimensions: data-driven decision-making, enhancement of HR functional effectiveness, strategic transformation of HR roles, and the identification of implementation challenges. The use of analytics allows organizations to make more accurate, objective, and timely decisions. It also enhances the efficiency and quality of core HR functions, including recruitment, training, and performance management. Furthermore, HR is increasingly positioned as a strategic partner that contributes to broader organizational decision-making and business outcomes. However, several challenges were identified, including limited analytical competencies among HR professionals, issues related to data quality, and organizational resistance to change, all of which may hinder effective implementation. This study contributes to the HRM literature by providing in-depth qualitative insights into the strategic value of Digital HR Analytics, while also emphasizing the need for developing analytical capabilities and robust digital infrastructure to maximize HR effectiveness in the digital era.